Drug delivery system: designing hydrogels as machinery for anti-inflammatory therapeutics from plant diversity of Ecuador - Zamora Mendoza, Lizbeth Carolina (2022)
Nowadays, several medicinal plants have been a natural source of pharmacological compounds. The present study extracted plant extracts (L001-M, L002-E, L003-M, and L004- E) by maceration in methanol and ethanol as solvents. The bioactive compounds were characterized by phytochemical screening to identify their secondary metabolites content. The functional groups corresponding to alkaloids, saponins, terpenes, flavonoids, phenols, and tannins were identified by FT-IR. In addition, thin layer chromatography techniques and UV/Vis spectra were used to analyze the components in the extracts. This research also evaluated the biological activity of the extracts in antimicrobial, antioxidant, and anti-inflammatory assays to analyze their potential pharmaceutical application. The minimum bactericidal concentration of samples L001-M and L002-E on Gram-negative bacteria Escherichia Coli was 2.5 mg/mL. The in vitro antioxidant activity was evaluated by the Ferric Reducing Power and Total Antioxidant Activity assay showing that the methanolic extracts (L001-M and C003-M) were better antioxidant compounds compared to the ethanolic extracts (L002-E and C004-E). In addition, inhibition of hypotonicity-induced hemolysis was positive for L001-M, L002-E, and C004-E. Cotton cellulose (NRC) and microcrystalline cellulose (MCC) hydrogels formulated with the four extracts were studied kinetically, structurally, and morphologically. The incorporation of the extracts into the hydrogels was verified by FT-IR assay and their analysis by stereoscope. Kinetic studies revealed that the MCC type showed better swelling values (45% to 140%) than the NRC hydrogels (49% to 95%). The release profiles of the extracts were also studied in PBS at pH 7.4, where the NRC type (50%) showed better results than the MCC hydrogel (30%). The effective biological activity of the hydrogels on the DH5-α cell line (E. coli) was recorded. The overall results suggest the effective encapsulation of the natural extracts in hydrogels as controlled release systems suggesting their possible biomedical application.